Pandemic Portrayed: Learning Style in Online Learning - Syilvia Wenny J; Yorina An’guna Bansa (STKIP PGRI Tulungagung, 2022)
Learning style is one of the most important factors in determining how students learn and has a significant effect on student learning strategies, which in turn affects their learning outcomes. It refers to the methods by which students collect, store, and extract material. Since pandemic came to all over the world, all od aspect in teaching and learning process is changing. It is included to students’s learning style. Some issues were discovered during online learning, especially in English learning for students at the University of Muhammadiyah Jambi. By these issues, it seems that there is a doubt of how they really learn from online learning. The aim of this study is to report data on the types of students' learning styles used in their English online learning. Data were analyzed using The VARK Questionnaire by Neil Fleming. This research uses the qualitative descriptive method. The population of this research was 1st semester of Management Department students in the academic year 2020. There were three classes; R.B1, R.A7 and R.B3. The result shows that the majority of students in this research used kinesthetic learning style. Then audio learning is the next place, then followed by reading and writing learning style. And the last is visual learning style.